2005
DOI: 10.1080/09593332608618474
|View full text |Cite
|
Sign up to set email alerts
|

Sustained and Complete Hexahydro-1,3,5-Trinitro-1,3,5-Triazine (RDX) Degradation in Zero-Valent Iron Simulated Barriers under Different Microbial Conditions

Abstract: Flow-through columns packed with "aged" zero-valent iron (ZVI) between layers of soil and sand were constructed to mimic a one-dimensional permeable reactive iron barrier (PRB). The columns were continuously fed RDX (hexahydro-1,3,5-trinitro-1,3,5-triazine, ca. 18 mg l(-1)) for over one year. Two columns were bioaugmented with dissimilatory iron reducing bacteria (DIRB) Shewanella algae BrY or Geobacter metallireducens GS-15 to investigate their potential to enhance the reactivity of aged iron by reductive dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…2004; Fuller et al. 2005; Shrout et al. 2005), and a number of micro‐organisms have been characterized that can degrade or transform RDX (Coleman et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2004; Fuller et al. 2005; Shrout et al. 2005), and a number of micro‐organisms have been characterized that can degrade or transform RDX (Coleman et al.…”
Section: Introductionmentioning
confidence: 99%
“…Of the nitroaromatic and nitramine explosives contaminants on these sites, hexahydro-1,3,5trinitro-1,3,5,-triazine (RDX) is known to migrate easily through soil into surface water and groundwater (Sheremata et al 2001;Clausen et al 2004;Davis et al 2004). Bioremediation of RDX in soils and groundwater has been demonstrated (Davis et al 2004;Fuller et al 2005;Shrout et al 2005), and a number of micro-organisms have been characterized that can degrade or transform RDX ammonium, formaldehyde and carbon dioxide (Fournier et al 2002;Jackson et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The catalytic activity of Fe +2 coordinated to oxides is believed to be the result of complexation of Fe +2 with surface hydroxyl groups and the formation of inner-sphere bonds, which increases the electron density of the adsorbed Fe +2 . Temporal monitoring of zero-valent iron surfaces during laboratory batch studies and field measurements of PRB have identified a wide range of iron minerals such as: akagenite, goethite, lepidocrocite, green rust, magnetite, ferrous sulfide, and maghemite [356,370,377]. Given that PRBs are emplaced at sites with widely differing groundwater chemistry, the suite of minerals that precipitate, as well as the rate of formation, can vary widely [372].…”
Section: Chemical Reduction Using Zero-valent Iron (Fe 0 ) Ferrous Imentioning
confidence: 99%
“…Although more than 150 PRBs have been installed worldwide [354], the majority of PRBs have been targeted for chlorinated compounds and only recently has research been aimed at using PRBs for environmental contaminants with multiple nitro groups (e.g., TNT, RDX, HMX) [60,339,[354][355][356][357][358][359][360]. Laboratory-based research on the destruction of explosives has provided support for using zero-valent iron in PRBs for field-scale treatment.…”
Section: Chemical Reduction Using Zero-valent Iron (Fe 0 ) Ferrous Imentioning
confidence: 99%
“…Mobile explosive contaminants, like RDX, threaten overall sustainability of Department of Defense (DoD) ranges by migrating away from the source areas and contaminating surface and subsurface soils at relatively low but potentially toxic levels. The potential for bioremediation of RDX in groundwater and soils via the addition of nutrients (19,23) or via combined abiotic/biotic processes (49) has been established. While in situ bioremediation is an attractive remedial action for these sites, the capability to predict the efficacy of in situ bioremediation of RDX is generally lacking.…”
mentioning
confidence: 99%